Neurothekeoma of the scalp in a child: A rare case - Aditya Pratap Singh; Maryem Ansari; Ramesh Tanger; Arun Kumar Gupta (Wolters Kluwer Medknow Publications, 2020)
Neurothekeoma (NT) is a rare, benign tumor that is derived from peripheral nerve sheath cells. There are less than 300 cases reported in the literature to date. Historically, this tumor has been subclassified as myxoid (classic), mixed, or the cellular type, depending on the amount of myxoid stroma and cellularity. Here, we present a case of NT (mixed type) of the scalp in a 3-year-old female child. The tumor was completely excised. No recurrence was detected in the past 3 months after the local excision.